Contraction of myofibrils in the presence of antibodies to myosin subfragment 2. - Harrington, W F (1990)
In a muscle-based version of in vitro motility assays, the unloaded shortening velocity of rabbit skeletal myofibrils has been determined in the presence and absence of affinity-column-purified polyclonal antibodies directed against the subfragment-2 region of myosin. Contraction was initiated by photohydrolysis of caged ATP and the time dependence of shortening was monitored by an inverted microscope equipped with a video camera. Antibody-treated myofibrils undergo unloaded shortening in a fast phase with initial rates and half-times comparable to control (untreated) myofibrils, despite a marked reduction in the isometric force of skinned muscle fibers in the presence of the antibodies. In antibody-treated myofibrils, this process is followed by a much slower phase of contraction, terminating in elongated structures with well-defined sarcomere spacings (approximately 1 micron) in contrast to the supercontracted globular state of control myofibrils. These results suggest that although the unloaded shortening of myofibrils (and in vitro motility of actin filaments over immobilized myosin heads) can be powered by myosin heads, the subfragment-2 region as well as the myosin head contributes to force production in actively contracting muscle.